Utilização de planejamento fatorial no estudo da remoção eletroquímica de íons Pb(II) de fluentes simulados - Almeida, Lucio César de (Universidade Federal de São Carlos, 2007)
In this work, the removal of Pb(II) ions from simulated wastewaters, using a flow-through cell under galvanostatic condition was studied. With help of factorial design and response surface methodology, the variables current, electrolyte flow rate and the specific surface area of the three-dimensional cathode used (stainless-steel wool AISI 304) were simultaneously investigated in order to optimize the electrochemical system. Firstly, the specific surface area of the stainless-steel wool used as three-dimensional cathode was estimated. Then, factorial designs were employed on the study of the removal of Pb(II) ions for different values of cathodic current, electrolyte flow rate and mass of the stainless-steel wool (consequently, distinct specific surface areas). Finally, the response surface methodology for optimization of the removal process and the analysis of variance (ANOVA) for evaluation of the quality of the developed fitting models were employed. Higher values of removal efficiency (RE) were obtained for the highest values of cathodic current; RE values above 90% were obtained after 30 min electrolysis. Higher values of current efficiency (CE) (22%) were obtained for intermediate values of current (~ 0.24 A). For values of current in the range of 0.24 to 0.31 A, the CE values were lower, due to occurrence of simultaneous reactions such as reduction of oxygen, water and nitrate. Low CE values were also obtained for current values in the range of 014 A to 0.24 A as not all surface area of the steel wool was operating under mass transport control. The response surfaces developed for RE and CE values as a function of the current and flow rate revealed that the region close to 0.25 A and 250 L h-1 was the best for the removal of Pb(II) ions. In these conditions, the RE and CE values were 93 % and 22 %, respectively. Although the concentration of Pb(II) decreased from 54 mg L-1 to 0.39 mg L-1 after 90 min electrolysis, almost 99 % of removal of Pb(II) ions was achieved after only 40 min electrolysis. A mass-transfer coefficient (km) of 1.8 x 10-5 m s-1 was obtained for the electrochemical reactor.
Use of factorial-design on the study of the electrochemical Removal of Pb(II) ions from simulated wastewaters
Keywords: Eletroquímica; Planejamento fatorial; Célula eletroquímica flow-through; Reator eletroquímico; Remoção de íons Pb(II); Eletrodo tridimensional; CIENCIAS EXATAS E DA TERRA::QUIMICA